Prone Team: A Large-Scale Prone Position Initiative During COVID-19 Pandemic. (April 2021) - Wells, Celia; Zhang, Ziya; Huelskamp, Stephen; Hughes, Ellen; Aguila, Dorothy; Sevillano, Maria; Garrett, Lisa; Acquah, Samuel; Chan, Christy; Kohli-Seth, Roopa
Abstract : AIM: To identify strategies to improve time to prone in ICUs during the coronavirus disease 2019 (COVID-19) pandemic for patients meeting the criteria for prone position ventilation. BACKGROUND: Healthcare systems worldwide experienced an influx of COVID-19 patients, especially in critical care. COVID-19 patients are at risk of acute respiratory distress syndrome (ARDS). Prone position ventilation is the standard of care for mechanically ventilated patients with moderate to severe ARDS. Prone maneuvers in and of itself are time-consuming and labor-intensive, posing additional risks to patients. APPROACH: Our academic medical center developed a travel proning team to address the rapid increase in COVID-19 patients with ARDS necessitating prone positioning. EVALUATION: Over a period of 30 days, 420 ICU patients were intubated, 131 had moderate to severe ARDS and underwent prone positioning. Patients were placed in prone position or returned to supine position more than 834 times over 38 days. At the highest point, 37 procedures were done in 24 hours. CONCLUSION: This quality initiative demonstrated that utilization of a traveling proning team provides efficiency in time to prone. Developing a travel prone team allowed for efficiency in time to prone, supported the ICU clinical teams, and enhanced interdisciplinary collaboration, which is essential during times of crisis. Abstract : Supplemental digital content is available in the text.